Mit Max Weber - Schluchter, Wolfgang (Mohr Siebeck, 2020)
"Even after a hundred years, Max Weber's works are still regarded as a viable research program. The ten essays collected here aim to demonstrate just this by providing a philosophical foundation for the research program and an interpretation of its major insights into the economic, scientific, political and religious developments of a secular age"--